Respuestas
Respuesta dada por:
13
Lim x²-3x+1/x²+2
x⇒-1
remplaza
1+3+1/1+2
=5/3
Lim x²-3x+1/x²+2 =5/3
x⇒-1
x⇒-1
remplaza
1+3+1/1+2
=5/3
Lim x²-3x+1/x²+2 =5/3
x⇒-1
oswalll9:
amigo puedes poner con todo el proceso por favor, gracias
Respuesta dada por:
10
Solo hay que sustituir el valor de "x"
![\frac{ x^{2} -3x+1}{ x^{2} +2} \\ \\ \frac{( -1)^{2}-3(-1)+1 }{ (-1)^{2}+2 } \\ \\ \frac{1+3+1}{1+2} \\ \\ \frac{5}{3} \frac{ x^{2} -3x+1}{ x^{2} +2} \\ \\ \frac{( -1)^{2}-3(-1)+1 }{ (-1)^{2}+2 } \\ \\ \frac{1+3+1}{1+2} \\ \\ \frac{5}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B+x%5E%7B2%7D+-3x%2B1%7D%7B+x%5E%7B2%7D+%2B2%7D++%5C%5C+%5C%5C++%5Cfrac%7B%28+-1%29%5E%7B2%7D-3%28-1%29%2B1+%7D%7B+%28-1%29%5E%7B2%7D%2B2+%7D++%5C%5C++%5C%5C++%5Cfrac%7B1%2B3%2B1%7D%7B1%2B2%7D++%5C%5C++%5C%5C++%5Cfrac%7B5%7D%7B3%7D+)
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años